Influence of COVID-19 on Environmental Awareness, Sustainable Consumption, and Social Responsibility in Latin American Countries - Valenzuela-Fernández, Leslier (2022)
This article aims to investigate the effect that COVID-19 has on environmental awareness, sustainable consumption, and consumer social responsibility. Although some recent research focused on this phenomenon, there are still no studies applied to Latin American consumers. In this study, the data comes from 1624 responses from Latin American consumers who also represent different generations, equitably distributed in 400 from Chile (24.6%), 421 from Colombia (25.9%), 401 from Mexico (24.7%), and 402 from Peru (24.8%). Data were collected through self-administered questionnaires using an online survey via Google Forms through email and social networks (Facebook, LinkedIn, Instagram, and WhatsApp) from July 2021 to September 2021. This study uses a quantitative methodology using a structural equations model (SEM) to examine the cause–effect relationships of the explanatory model of this study. The main findings indicate that consumers from these countries declare that their behaviors have become ecologically and socially responsible. In addition, these respondents indicated that they had increased their interest in sustainable consumption and in ac quiring environmentally friendly products to reduce waste and negative impacts on the environment derived from consumption. Based on the results, this research provides useful information to change or re-direct the communication and strategies of governments, brands, organizations, and society to promote actions and behaviors that help reduce the negative impact on the environment derived from consumption in a Latin American market. Managerial implications are provided.